205 Evaluation of a Direct Fed Microbial and/or an Enzymatically Hydrolyzed Cell Wall + Yeast Culture Product on Growth Performance, Dietary Net Energy Utilization, and Carcass Traits in Beef Steers. (12th April 2022) - Gubbels, Erin; Rusche, Warren C; Rehberger, Tom G; Block, Elliot; Smith, Zachary K
Abstract: This research determined the influence a direct fed microbial (DFM) and/or enzymatically hydrolyzed yeast (EHY) product (both from Arm & Hammer Animal and Food Production, Princeton, NJ) have on growth performance and carcass characteristics in beef steers fed in the Northern Plains (NP). Single-sourced, newly weaned steers (n = 256; initial BW = 246 ± 1.7 kg; n = 8 pens/treatment with 8 steers/pen) were blocked by location in a 2×2 factorial treatment arrangement of DFM (Certillus CP B1801 dry; Bacillus subtilis, Lactobacillus plantarum ; 28 g/steer·d -1 ) and EHY (Celmanax; 18 g/steer·d -1 ). Steers were individually weighed on d 1, 14, 42 (end of receiving phase; implant with 200 mg progesterone and 20 mg estradiol benzoate), 77, 105 (end of growing phase), 133, 161 (implant with 200 mg trenbolone acetate and 28 mg estradiol benzoate), 182, 230 (start ractopamine HCl at 300 mg/steer·d -1 ) and 258. No DFM × EHY interactions ( P ≥ 0.05) were observed for cumulative growth performance. No health parameters were influenced by treatment ( P ≥ 0.08). EHY steers had reduced ( P = 0.04) dry matter intake compared with DFM and had a tendency ( P < 0.08) for improved applied energetics measures. A DFM × EHY interaction ( P = 0.02) was noted for the distribution of USDA yield grade (YG) 1 carcasses. Control steers had a greater proportion ( P < 0.05) of YG1 carcasses compared with other treatments. A DFM × EHY interaction ( P = 0.04) was noted for the distribution of USDA Prime carcasses. Steers from DFM × EHY had a greater proportion (P < 0.05) of USDA Prime carcasses compared with DFM or EHY, but did not differ from control, which were similar to DFM and EHY. Use of DFM and EHY alone or in combination had minimal effects on growth performance and carcass traits in NP steers.